2010
DOI: 10.1155/2010/829190
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxon Attenuates Vascular Smooth Muscle Contraction through Inhibiting Ca2+Influx in the Rabbit Thoracic Aorta

Abstract: We investigated the effect of paraoxon on vascular contractility using organ baths in thoracic aortic rings of rabbits and examined the effect of paraoxon on calcium homeostasis using a whole-cell patch-clamp technique in isolated aortic smooth muscle cells of rabbits. The findings show that administration of paraoxon (30 μM) attenuated thoracic aorta contraction induced by phenylephrine (1 μM) and/or a high K+ environment (80 mM) in both the presence and absence of thoracic aortic endothelium. This inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Organophosphate (OP) insecticides are used commercially (agriculture and industries) and domestically (in homes) to control pests (Zhou et al, 2010). In addition to the toxic effects of OPs on different tissues (Zhou et al, 2010), research has reported that they have effects on the circulatory system (Guvenic Tuna et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organophosphate (OP) insecticides are used commercially (agriculture and industries) and domestically (in homes) to control pests (Zhou et al, 2010). In addition to the toxic effects of OPs on different tissues (Zhou et al, 2010), research has reported that they have effects on the circulatory system (Guvenic Tuna et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate (OP) insecticides are used commercially (agriculture and industries) and domestically (in homes) to control pests (Zhou et al, 2010). In addition to the toxic effects of OPs on different tissues (Zhou et al, 2010), research has reported that they have effects on the circulatory system (Guvenic Tuna et al, 2011). Some studies reported that acute and chronic toxicity of OPs lead to the degeneration of collagenous and elastic fibers of the vascular wall (Akimov and Kolesnichenko, 1985;Antov et al, 1984;Yavuz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Diazinon causes a serious damage to different tissues either in human and animals such as neurotoxicity, myocardial injury, cytotoxicity and other systemic dysfunctions by inhibition of acetyl cholinesterase and up regulation of its receptors due to acetylcholine accumulation [8].…”
Section: Egypt J Vet Sci (Special Issue) (2021) Aseel Kamil Hameed and Jihad Abdulameer Ahmedmentioning
confidence: 99%
“…DZN is an organophosphate insecticide widely used around the world to control insects in agriculture. Although the main mechanism of DZN toxicity is the inhibition of acetylcholinesterase (AChE) [8], however, recent studies have shown that acute and chronic toxicity of DZN induce oxidative stress leading to generation of free radicals and change in antioxidants or ROS scavenging enzymes in different tissues such as cardiovascular system [9][10][11][12]. Crocin is a carotenoid isolated from Crocus sativus L. (saffron).…”
mentioning
confidence: 99%